Toxicity of 32.2 kDa MW Escherichia coli Pili Adhesin Isolated from Infertile Male Semen in Reproductive System - Sukarjati, Sukarjati; Amilah, Susie; Sudjarwo, Sudjarwo (Folia Medica Indonesiana, 2018)
Escherichia coli (E. coli) is the leading cause of male genital tract infection with no symptoms of infertility. Protein E. coli pili hemagglutinin isolated from infertile male sperm with 32.2 kDa MW acts as adhesion in spermatozoa. This study aimed to prove whether E. coli pili adhesin 32.2 kDa MW is toxic to male reproductive system. Samples consisted of spermatozoa of 30 guinea pigs divided into three groups: control, immunized with E. coli pili adhesin 32.2 kDa MW protein, and transurethral infected E. coli. Observations of sperm motility, vitality and morphology were performed under a microscope. MDA levels and sperm DNA damage were measured by a spectrophotometer and comet assay method and observed using a fluorescent microscope. There was no difference between control and immunization group of E. coli pili adhesin in motility (p=0.499), vitality (p=0.817) and morphology (p=0.176); between control and transuretral infection groups in motility (p=0.000), vitality (p=0.000) and morphology (p=0.000); and between control and both treatment groups in motility (p=0.001), vitality (p=0,000) and morphology (p=0.000). Histologic analysis showed E. coli pili adhesin of 32.2 kDa MW immunization group did not suffer from testicular tissue damage, while the positive group showed a deterioration of seminiferous tubular cells. MDA levels differed between immunization group E. coli pili, transurethral infection group, and control (p=0.024) and between transurethral and control (p=0.007) groups. However, between control and immunized group with E. coli pili protein showed no difference (p=0.251). DNA damage differed (p=0.000) between immunized group with E. coli pili, transurethral infection and control group; between control and transurethral infected group (p=0.000); and between transurethral infection group and E. coli pili protein immunization group (p=0.000). However, between control and E. coli pili immunization group showed no difference (p=0.600). In conclusion, E. coli pili adhesin 32.2 kDa MW protein is not toxic for sperm quality and the quality of sperm molecules.